Effectiveness of the strategy of Precious Pages Corporation in translating best seller english novels in Tagalog to the buying decision of college students around SM City Manila - Fabi, Francis Jayvincent P. Guia,Princess J. Malicdem, Kristelle Anabelle A. Rivera, Sear Jan L. and Timbol, Mark S. 4 0 16; 5 (2013)
u
Research Paper: (BSBA major in Marketing Management) - Pamantasan ng Lungsod ng Maynila 2013.
Keywords: 2 -- 0; 6; 20; 20; 2